Task Shifting for Initiation and Monitoring of Antiretroviral Therapy for HIV-Infected Adults in Uganda: The SHARE Trial. (1st March 2021) - Sekiziyivu, Brian Arthur; Bancroft, Elizabeth; Rodriguez, Evelyn M.; Sendagala, Samuel; Nasirumbi, Muniina Pamela; Najjengo, Marjorie Sserunga; Kiragga, Agnes N.; Musaazi, Joseph; Musinguzi, Joshua; Sande, Enos; Brad, Bartholow; Dalal, Shona; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: With countries moving toward the World Health Organization's "Treat All" recommendation, there is a need to initiate more HIV-infected persons into antiretroviral therapy (ART). In resource-limited settings, task shifting is 1 approach that can address clinician shortages. Setting: Uganda. Methods: We conducted a randomized controlled trial to test if nurse-initiated and monitored ART (NIMART) is noninferior to clinician-initiated and monitored ART in HIV-infected adults in Uganda. Study participants were HIV-infected, ART-naive, and clinically stable adults. The primary outcome was a composite end point of any of the following: all-cause mortality, virological failure, toxicity, and loss to follow-up at 12 months post-ART initiation. Results: Over half of the study cohort (1, 760) was women (54.9%). The mean age was 35.1 years (SD 9.51). Five hundred thirty-three (31.6%) participants experienced the composite end point. At 12 months post-ART initiation, nurse-initiated and monitored ART was noninferior to clinician-initiated and monitored ART. The intention-to-treat site-adjusted risk differences for the composite end point were −4.1 [97.5% confidence interval (CI): = −9.8 to 0.2] with complete case analysis and −3.4 (97.5% CI: = −9.1 to 2.5) with multiple imputation analysis. Per-protocol site-adjusted risk differences were −3.6 (97.5% CI: = −10.5 to 0.6) for complete case analysis and −3.1 (−8.8 to 2.8) for multiple imputation analysis. This difference was within hypothesized margins (6%) for noninferiority. Conclusions: Nurses were noninferior to clinicians for initiation and monitoring of ART. Task shifting to trained nurses is a viable means to increase access to ART. Future studies should evaluate NIMART for other groups (e.g., children, adolescents, and unstable patients).